The experience of suburban modernity : how private transport changed interwar London - Law, Michael John (Manchester University Press, 2014)
This title explores how the adoption of new forms of private transport transformed inter-war suburban London. It shows how London's suburban middle classes used their newly found disposable income to enjoy driving, motorcycling and flying. It demonstrates that these new practices were welcomed by many, but met resistance to change from those who were dismayed by the accidents that resulted from increased mobility and the aesthetic and cultural changes that were the consequence of Americanization and suburban development.
Keywords: Suburbs -- England -- London -- History -- 20th century.; Suburban life -- England -- London -- History -- 20th century.; Urban transportation -- England -- London -- History -- 20th century.; London (England) -- Social conditions -- 20th century.; London (England) -- Social life and customs -- 20th century.; Banlieues -- Angleterre -- Londres -- Histoire -- 20e siècle.; Vie de la banlieue -- Angleterre -- Londres -- Histoire -- 20e siècle.; Transports urbains -- Angleterre -- Londres -- Histoire -- 20e siècle.; Londres (Angleterre) -- Mœurs et coutumes -- 20e siècle.; BUSINESS & ECONOMICS -- Industries -- Transportation.; TRANSPORTATION -- Public Transportation.; Manners and customs; Social conditions; Suburban life; Suburbs; Urban transportation; England -- London; 1900-1999; Inter-war.; London.; Mobilities.; Modernity.; Suburbia.; Transport.; History